Feedforward control design for finite-time transition problems of nonlinear systems with input and output constraints - Graichen, Knut; Zeitz, Michael (IEEE Transactions on Automatic Control, 2008)
The article extends a recently presented approach to feedforward control design for nonlinear systems to additionally account for input and output constraints. The inversion-based design treats a finite-time transition problem as a two-point boundary value problem (BVP) in the coordinates of the input-output normal form. To account for constraints on the output and its time derivatives, the input-output dynamics is replaced by a new system, which is systematically constructed by means of saturation functions. The solvability of the BVP requires a sufficient number of free parameters in an ansatz function. The resulting BVP with free parameters can be solved in a straightforward manner (e.g., with the Matlab function bvp4c). Input constraints can additionally be considered as constraints on the highest output derivative. The approach is applicable to nonlinear and nonminimum-phase systems, which is illustrated for the side-stepping of an inverted pendulum on a car
Keywords: Boundary value problem; input and output constraints; input–output normal form; nonlinear feedforward control; trajectory planning; Control design; Nonlinear systems; Control systems; Trajectory; Automatic generation control; Boundary value problems; Nonlinear dynamical systems; Feedback loop; Tracking loops; Actuators